The impact of digital transformation adoption towards broadcasting industry in Sri Lanka - Samarakoon, S.M. Darshitha Diyanath; Johar, Md Gapar Md; Khatibi, Ali (Journal of Print and Media Technology Research, 2023)
Sri Lanka’s media landscape follows the global broadcasting industry’s popularity. Digitalization has had the greatest impact on the sector and all its usage scenarios. Therefore, the primary goal of this study is to ascertain how Sri Lanka’s broadcast business would be impacted by the digital revolution. This study seeks to uncover the factors that influence the media industry’s transition to a digital model and determine how much viewers, broadcasters, content providers, and infrastructure in Sri Lanka depend on public digital media use. A standardized questionnaire has been administered to reach the goal. From a sample of 1 174 respondents in the Western Province, information about the nine research constructs was gathered using previously validated instruments SmartPLS 3 and the SPSS 26 that were used to systematically assure the empirical validation of the theoretical model. The conceptual framework did not match the research’s real-world reality. Digital broadcasts and digital literacy affect broadcasters’ digital uptake. User device availability, price, and perceived ease of use mediate the intention to use a digital device. Perceived usefulness partially mediates broadcast user digital adoption. Age and gender moderating variables, produced from solid empirical findings and fully excluded from the study, established a new field of study for the literature. The findings also omit the independent policy on digitalization variable. Hence, the study showed that its survey results had a considerable impact on the conceptual model compared to past empirical investigations, and most importantly, it opened up a new field of knowledge for future research. Lastly, the study’s findings were discussed and recommendations are provided. Sri Lanka’s media industry’s digital transformation will benefit from applying the research’s findings. The proper application of the research’s conclusions will improve the sector by bringing about several advantages for Sri Lanka’s media industry’s digital transformation.